PR65A Phosphorylation Regulates PP2A Complex Signaling - Kotlo, Kumar (Public Library of Science, 2014)
Serine-threonine Protein phosphatase 2 A (PP2A), a member of the PPP family of phosphatases, regulates a variety of essential cellular processes, including cell-cycling, DNA replication, transcription, translation, and secondary signaling pathways. In the heart, increased PP2A activity/signaling has been linked to cardiac remodeling, contractile dysfunction and, in failure, arrythmogenicity. The core PP2A complex is a hetero-trimeric holoenzyme consisting of a 36 kDa catalytic subunit (PP2Ac); a regulatory scaffold subunit of 65 kDa (PR65A or PP2Aa); and one of at least 18 associated variable regulatory proteins (B subunits) classified into 3 families. In the present study, three in vivo sites of phosphorylation in cardiac PR65A are identified (S303, T268, S314). Using HEK cells transfected with recombinant forms of PR65A with phosphomimetic (P-PR65A) and non-phosphorylated (N-PR65A) amino acid substitutions at these sites, these phosphorylations were shown to inhibit the interaction of PR65A with PP2Ac and PP2A holoenzyme signaling. Forty-seven phospho-proteins were increased in abundance in HEK cells transfected with P-PR65A versus N-PR65A by phospho-protein profiling using 2D-DIGE analysis on phospho-enriched whole cell protein extracts. Among these proteins were elongation factor 1α (EF1A), elongation factor 2, heat shock protein 60 (HSP60), NADPH-dehydrogenase 1 alpha sub complex, annexin A, and PR65A. Compared to controls, failing hearts from the Dahl rat had less phosphorylated PR65A protein abundance and increased PP2A activity. Thus, PR65A phosphorylation is an in vivo mechanism for regulation of the PP2A signaling complex and increased PP2A activity in heart failure.